A case of biopsy-proven cardiac sarcoidosis without any other extracardiac manifestations - Ikeuchi, Masaki (J Cardiol Cases, 2011)
A 49-year-old woman was referred to our hospital for uncontrollable heart failure. She had never been diagnosed as having sarcoidosis. Chest X-ray showed cardiomegaly without bilateral hilar lymphadenopathy. Echocardiography showed diffuse hypokinesis of the left ventricle mimicking idiopathic dilated cardiomyopathy. No specific manifestations implying sarcoidosis were observed. On cardiac catheterization, coronary angiograms were normal, whereas concurrent routine endomyocardial biopsy showed foci of non-caseating granuloma, indicating sarcoidosis. Pathological finding was the only clue to diagnose cardiac sarcoidosis among our standard examinations for heart failure. No other additional investigations found any extracardiac features of sarcoidosis. All serological and immunological examinations were within normal range. This is a challenging case of biopsy-proven cardiac sarcoidosis without any other extracardiac involvement.